Innovation and Creativity in Organizations - Anderson, Neil; Potočnik, Kristina; Zhou, Jing (Journal of Management, 2014)
Creativity and innovation in any organization are vital to its successful performance. The authors review the rapidly growing body of research in this area with particular attention to the period 2002 to 2013, inclusive. Conceiving of both creativity and innovation as being integral parts of essentially the same process, we propose a new, integrative definition. We note that research into creativity has typically examined the stage of idea generation, whereas innovation studies have commonly also included the latter phase of idea implementation. The authors discuss several seminal theories of creativity and innovation and then apply a comprehensive levels-of-analysis framework to review extant research into individual, team, organizational, and multilevel innovation. Key measurement characteristics of the reviewed studies are then noted. In conclusion, we propose a guiding framework for future research comprising 11 major themes and 60 specific questions for future studies.